Occurrence of Enterobacteriaceae in Raw Meat and in Human Samples from Egyptian Retail Sellers. (11th November 2014) - Gwida, Mayada; Hotzel, Helmut; Geue, Lutz; Tomaso, Herbert
Abstract : The present study was performed to assess the presence of Enterobacteriaceae in raw meat and handlers in Egypt using cultivation and matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). A total of 100 raw meat samples (chicken and beef meat, 50 each) were randomly purchased from butchers and local meat retailers located at Mansoura city, Egypt. Fifty human samples were collected from meat handlers (hand swabs and stool specimens, 25 each). 228 bacterial isolates were recovered from these samples. Unidentified isolates were characterized by partial 16S rRNA gene sequencing. Escherichia coli isolates were further typed using a DNA microarray system. Proteus spp. (60.0%) were found to be the most abundant followed by Escherichia coli (38.7%), Klebsiella spp. (17.3%), and Citrobacter spp. (13.3%). The presence of different Enterobacteriaceae in locally produced retail raw meat demonstrates the risk of infection of people through consumption of raw or undercooked meat and the risk for cross-contamination of other food products. Harmonized and concerted actions from veterinary and public health authorities are needed to reduce the risk of infection.